Narrations déviantes : l'intimité entre femmes dans l'imaginaire français du dix-septième siècle - Legault, Marianne (Presses de l'Université Laval, 2008)
Si les rapports intimes entre les femmes ont toujours existé, comment expliquer leur absence dans le discours critique littéraire français malgré la foulée des études récentes sur les femmes, des études gays et lesbiennes et des études queers ? Voulant remédier à cette absence, ce livre retrace une généalogie de l’intimité féminine dans la littérature française du dix-septième siècle. Suivant une lecture qui s’inspire des études lesbiennes et queers, il explore l’effet d’un héritage androcentré sur l’intimité féminine au Grand Siècle, telle qu’elle a été envisagée par l’imaginaire d’Honoré d’Urfé dans L’Astrée et d’Isaac de Benserade dans Iphis et Iante. L’anxiété masculine qui se dégage de leurs représentations contraste avec la célébration de l’intimité féminine chez Madeleine de Scudéry dans Mathilde (d’Aguilar) et chez Charlotte-Rose de Caumont de La Force dans Plus belle que fée, deux œuvres qui élargissent les possibilités érotiques au sein des rapports intimes entre femmes au-delà de ce que les écrivaines avaient auparavant osé.
Keywords: 1600-1699; approches et analyses; arts; discipline; discours dominant; europe; france; identités LGBTQIA2+; patriarcat; personnes lesbiennes; périodes historiques; queer; régions géographiques; sexisme; systèmes d'oppressions; études littéraires

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Macmillan, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques